Death by hot apple cider - Erickson, Alex (Erickson, Alex. Bookstore café mystery, 2021)
"With autumn in full swing and Thanksgiving on the way, Krissy's supplying cider and her staff is manning the apple-bobbing booth at a town event. But then a patron dunks his head in -- and doesn't come back up. It soon becomes clear that Krissy's brew wasn't to blame. But with her policeman boyfriend looking to make detective, she can't help being drawn into the investigation. The victim was notorious for harassing not only her own bookstore but the library and the school for promoting supposedly scandalous literature -- before someone censored him permanently. Now, Krissy will have to check out a stack of suspects to find a killer who's rotten to the core ..." -- Page 4 of cover.